ANALISIS SIVA MELALUI KEPUASAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA PT. HADJI KALLA CABANG ALAUDDIN MAKASSAR - Tiong, Piter; Soemaryo, Partono; Fatma, Nur (Jurnal Metaverse ADPERTISI, 2024)
The purpose of this research is to determine the influence of Solutions, value, information and access on customer satisfaction and loyalty, as well as to determine and analyze the influence of Solutions, information, value and access on customer loyalty through customer satisfaction at PT. Haji Kalla Makassar Branch. This research uses a quantitative approach, by taking samples, namely customers who bought Toyota cars, which were determined to be 100 respondents, data collection techniques using questionnaires, observation and documentation. Meanwhile, the data analysis technique uses path analysis. The research results found that solution, Information, Value and Access had a positive and significant influence on customer satisfaction and customer loyalty, customer satisfaction had a positive and significant influence on customer loyalty. Meanwhile, from the results of the mediation test, it was found that customer satisfaction can mediate the influence of solution, information, value and access on customer loyalty at PT. Hadji Kalla Alauddin Branch, Makassar.